PENINGKATAN AKTIVITAS BELAJAR SISWA MELALUI MODEL PROBLEM POSING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS IV SDN 269 RANTOBI - Sukri Nasution (Universitas Negeri Medan, 2017)
ABSTRACT : Increasing Student Learning Activity Through Problem PosingModel In Islamic Religious Education Elementary Class IV SDN 269 Rantobi. The subjects of class IV SDN 269 Rantobi with the number of students 14 people. This research was conducted by applying Problem Posing learning model for two cycles and each cycle consisted of two meetings. By applying the learning model Problem Posing student learning outcomes from cycle to next cycle experience improvement. Student learning result of KKM is complete in formative I 9 (64,2%) student and formative II 13 (92,8%) student. The average score of students' understanding on the subject at cycle I 57.1 and in cycle II increased to 80.Keywords : Problem Posing, Learning ActivityABSTRAK : Peningkatan Aktivitas Belajar Siswa Melalui Model Problem Posing Pada Mata Pelajaran Pendidikan Agama Islam Kelas IV SDN 269 Rantobi. Subjek penelitian kelas IV SDN 269 Rantobi dengan jumlah siswa 14 orang. Penelitian ini dilakukan dengan menerapkan model pembelajaran Problem Posing selama dua siklus dan masing-masing siklus terdiri dari dua kali pertemuan. Dengan menerapkan model pembelajaran Problem Posing hasil belajar siswa dari siklus ke siklus berikutnya mengalami peningkatan. Hasil belajar siswa tuntas KKM pada formatif I 9 (64,2%) siswa dan formatif II 13 (92,8%) siswa. Nilai rata-rata pemahaman siswa pada materi pada siklus I 57,1 dan pada siklus II meningkat menjadi 80.Kata Kunci : Problem Posing, Aktivitas Belajar